SURGICAL MANAGEMENT OF PROXIMAL TIBIAL FRACTURE IN A SPITZ: A CASE REPORT - Das, B C; Prasad, A Arun; Kumar, R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Fractures of the tibia and fibula are fairly common injuries in small animal practice (Denny and Butterworth, 2000) and the tibial diaphysis is the most common location for a fracture (Zaal and Hazewinkel,1996). Gorse (1998) stated proximal fractures of the tibia are least common (7%). A number of fixation methods are available for tibial shaft fracture repair, each of which has differing advantages and disadvantages. The chosen method of fixation should achieve adequate alignment and stability of the fragments for the duration of the healing period. In puppies and kittens under 6 months of age crossed Kirschner wires are used for fixation of distal femoral fractures (Sumner-Smith and Dingwall, 1973). The present case study successfully managed by cross pinning of proximal tibial fracture in a dog.